Prevalence and predictors of supportive care needs in lung cancer patients. (1st April 2011) - Buchanan, D; Milroy, R; Baker, L; Thompson, A M; Levack, P
Abstract : Abstract: Introduction: Lung cancer is a disease of high symptom distress, increased psychosocial burden, short survival and a high mortality. The Palliative Outcome Scale (POS) can be used to assess individuals' supportive care needs. Aims: To evaluate lung cancer patients' supportive care needs and predictors of increased supportive care needs. Methods: Patients completed questionnaires on any visit. Total POS score and prevalences of individual items and were calculated. Demographics and clinical variables were recorded. Predictors of increased supportive care needs were evaluated using logistic regression. Results: Of 353 patients, 303 fully completed POS. At least one unmet supportive care need was identified in 97.4% of patients. POS x =9.81 (SD5.87, 95%CI 9.15 to 10.47). Prevalence of moderate to severe symptoms were: 56.9% perceived support network anxiety, 45.6% personal anxiety, 40.8% pain, 30.5% had unmet information needs, 29.6% reduced self-esteem, 20.1% practical matters needed addressed, 21.2% able to share feelings occasionally or less, 17% affected by 'other' symptoms, 12.1% low life-worth and 9.6% felt at least ½ a day had been wasted through healthcare appointments. An increased POS score was significantly predicted by: poor performance status (PS=2, OR 3.99 CI 1.83 to 8.70; PS=3–4, OR 7.62 CI 3.49 to 16.61), age less than 65 years (OR 0.37 CI 0.19 to 0.73) and presence of increasing respiratory symptoms (OR 1.48 CI 1.23 to 1.78). There was no significant effect from gender, histology, stage, time from diagnosis, treatment type or deprivation category. Conclusion: Lung cancer patients have significant supportive care needs. Poorer physical function, younger age and presence of respiratory symptoms predict increased needs.